Efficacy of Fagara zanthoxyloides and Kigelia africana Extracts in Protecting Sugarcane Against Subterranean Termites - Lamidi, A. A.; Oni, M. O. (Journal of Science, Technology and Innovation Research, 2026)
The efficacy of aqueous extracts from Fagara zanthoxyloides and Kigelia africana was evaluated and compared to the insecticide, Dichlorvos (DDVP), for controlling termite Infestation in sugarcane field experiment. The experimental materials used for the study were obtained from FUTA Teachig and Research farm and National Centre for Genetic Resources and Biotechnology (NACGRAB), Ibadan, Oyo State. Results revealed that extract of F. zanthioxyloides at 60% concentration promoted the highest sprouted setts in the 4th, 5th and 6th weeks after planting (WAP). However, the control treatment showed the highest percentage sett establishment of 94.44% which was significantly dfferent from the botanical treatments. At 20th WAP, sugarcane treated with F. zanthoxyloides extract at 60% concentration produced the highest number of tillers which was significantly different from the other treatments. Similarly, this same treatment F. zanthoxyloides resulted in the highest number of leaves at 10th, 15 and 20th WAP and there were no signifant difference among the other treatments. For plant height evaluated, K. africana extract at 80% concentration recorded the highest values at the 10th and 15th WAP. The largest leaf area was observed in setts treated with F. zanthoxyloides extract at 60% concentration followed by its 40% concentration and they were significantly different from the other treatments. The study demonstrates that extracts from both K. africana and F. zanthoxyloides can effectively function as botanical termicides to protect sugarcane against subterranean termite Infestation in the field.